Culture in Sociological Depiction - Gruchoła, Małgorzata (Roczniki Kulturoznawcze, 2010)
The goal of the publication is to analyse the definition and the conception of the culture in the area of sociology. The subject of the detailed consideration includes the following research issues: definitions of culture (nominal, historical, normative, psychological, structural, genetic), culture vs nature, culture as a subject interesting for sociology (types, categories, kinds of culture, message arrangement), culture as the research subject for culture sociology (symbolic culture, criteria for differentiation of the sphere of social and cultural phenomena, determination of mutual relations of these two spheres). The article is summarized with conclusions.